Longitudinal association of body mass index and waist circumference with left ventricular mass in hypertensive predialysis chronic kidney disease patients - Stel, Vianda S. (Oxford University Press, 2013)
BACKGROUND: This study aimed to investigate the association of both body mass index (BMI) and waist circumference (WC) with left ventricular mass (LVM) in hypertensive predialysis chronic kidney disease (CKD) patients. METHODS: From 2004 to 2005, 206 consecutive incident adult patients from the outpatient CKD clinics of two hospitals in Greece were included. Inclusion criteria were the presence of CKD and hypertension. BMI (kg/m(2)), WC (cm) and LVM (g) were assessed annually for 3 years. RESULTS: The mean age was 68.1 years, mean BMI 29.1 kg/m(2) and mean WC was 103.7 cm. The median LVM was 245.7 g (n = 179). In the cross-sectional data, linear regression models showed that WC {β = 1.2 [95% confidence interval (CI) 0.15; 2.3]}, and not BMI [β = 2.1 (95% CI: −0.70; 4.8)], was significantly associated with LVM. After adjustment for age, sex, primary renal disease, smoking and history of cardiovascular disease, both BMI [β = 4.7 (95% CI: 2.0; 7.4] and WC [β = 1.2 (95% CI: 0.14; 2.3)] were significantly associated with LVM. These associations were pronounced in CKD stage 1–3, but not in CKD stage 4–5. In the longitudinal analysis, linear mixed models adjusting for confounders showed that both an increase in BMI [β = 2.9 (95% CI: 0.74; 5.1)] and an increase in WC [β = 1.1 (95% CI: 0.28; 1.8)] were significantly associated with an increase in LVM. CONCLUSIONS: In hypertensive predialysis CKD patients, both BMI and WC were associated with LVM in CKD stage 1–3, but not in CKD stage 4–5. In the longitudinal analysis, both an increase in BMI and WC were associated with an increase in LVM. Future studies should focus on mechanisms responsible for the associations between anthropometric variables and LVM.